2019
DOI: 10.1029/2018jd029052
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Model for the Streamwise Velocity in the Near‐Neutral Atmospheric Surface Layer

Abstract: For the reconstruction of the streamwise velocity field in the high‐Reynolds‐number (Reτ ≈ Ο(106)) near‐neutral atmospheric surface layer (ASL), a predictive model was proposed in our work. In our model, the streamwise velocity time series at each height are predicted by the superposition of mean velocity, small‐scale turbulent signals, and large‐scale turbulent signals. All the parameters used by our model have clear physical meaning. In addition, the parameters can be directly determined by the experiment th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The previously documented maximum Reynolds number is = 647 (Ji, Munjiza, Avital, Xu & Williams, 2014). Even if the Lagrangian point-particle method is employed (Sardina et al, 2012;Vreman, 2007;Zhao, Andersson, & Gillissen, 2013), the highest Reynolds number currently achievable is also limited to (10 3 ) (Richter, 2015; Wang & Richter, E5-4 H. Liu and X. Zheng 2019). To improve the Reynolds number, the LES may be a feasible approach, but currently, there is no general model for describing particle-laden turbulence at high Reynolds numbers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previously documented maximum Reynolds number is = 647 (Ji, Munjiza, Avital, Xu & Williams, 2014). Even if the Lagrangian point-particle method is employed (Sardina et al, 2012;Vreman, 2007;Zhao, Andersson, & Gillissen, 2013), the highest Reynolds number currently achievable is also limited to (10 3 ) (Richter, 2015; Wang & Richter, E5-4 H. Liu and X. Zheng 2019). To improve the Reynolds number, the LES may be a feasible approach, but currently, there is no general model for describing particle-laden turbulence at high Reynolds numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 16. Comparison between the model prediction results and measured results at (a) 0.9 m; (b) 1.71 m; (c) 7.15 m; and (d) 30 m, taken fromHan, Liu, et al (2019).…”
mentioning
confidence: 99%
“…(), and Han et al. (). Data validations by Wang and Zheng () confirmed that the selected ASL data exhibit properties that are typical of canonical TBL flows in general and thus can be used in studies of high‐Reynolds‐number wall turbulence.…”
Section: Asl Observations and Data Processingmentioning
confidence: 99%
“…Extended AR models for multivariate situations combined with data clustering methods were used to investigate interactions between motions with distinct characteristic scales (Vercauteren & Klein 2015;Vercauteren, Mahrt & Klein 2016;Vercauteren et al 2019). Moreover, the ARMA model and its combination with other statistical models can be used to analyse and predict non-stationary ASL turbulence (Zhang et al 2023).…”
Section: Introductionmentioning
confidence: 99%